Development of a method for predictive calculations density of ionic liquids in a wide range of temperature and pressure - Nathan Sombra Evangelista (2014)
Ionic liquids are compounds of considerable interest due to their unique physicochemical properties. A detailed knowledge of these properties is of great importance. In particular, the liquid density is a very important property required in many design problems and, therefore, in process simulation . Experimental measurements of this property is not viable for all the existing ionic liquids . Therefore, development of new methods for its estimation is essential. In this work , a new group contribution model capable of estimating ionic liquids density over a wide range of temperatur e (251.62 â 473. 15 K) is proposed. This method ( â GCVOL - IL â ) is an extension of a reliable existing method ( âGCVOL - OL - 60â ) able to estimate the same property for organic molecular compounds at several temperatures and atmospheric pressure . Estimation of density at higher pressures (up to 300 MPa) was performed by the use of a Tait - type equation. A large databank containing 21845 experimental density data for 863 pure ionic liquids and 994 experimental data for 15 different binary mixtures of these com pounds has been applied in the development of this work . The results presented indicated that the model was able to estimate the volumetric behavior (T, P, ρ ) of various ionic liquids ( including policationic species) and of binary mixtures containing these compounds (x, T, ρ ) . The method has been compared to the best existing group contribution models able to estimate the same property. The analysis of different criteria encourage s the application and implementation of the proposed method in process simulators.